How the body tells the story: using the nonverbal cues of trauma between mothers and toddlers to mark a change in maternal attitudes during Clinician-Assisted Videofeedback Exposure Sessions - Tortora, Suzi; Schechter, Daniel Scott (Frontiers in Psychology, 2025)
IntroductionThis study aims to examine what a form of video-based analysis of nonverbal communication: “Dyadic Attachment-based Nonverbal Communicative Expressions (DANCE)” can reveal about change in the bodies of interpersonal violence-exposed mothers who suffer from posttraumatic stress disorder. DANCE, developed by a dance-movement therapist (first author) was applied to video excerpts from a videofeedback, exposure- and mentalization-based, manualized intervention. This intervention, Clinician-Assisted Videofeedback Exposure Session(s) (CAVES),” developed by a child and adolescent psychiatrist (second author), involves the filming of mother-infant interactions. It has empirically shown a change in these mothers’ perception of their young children, as expressed verbally, but has not yet been examined for accompanying changes in behavior.MethodsFollowing an introduction to the theoretical premises and historical context of both DANCE and CAVES and the latter’s related 16-session manualized psychotherapy “Clinician-Assisted Videofeedback Exposure Approach Therapy (CAVEAT),” case vignettes of two mothers who underwent the CAVES with their toddlers are presented qualitatively.ResultsTwo case-naïve raters observed significant changes in body tone, posture, gestures and facial expression in line with previous findings of reduction of negativity of maternal attributions towards the children.DiscussionImplications for further research based on these qualitative results include consideration of (1) how the DANCE video microanalysis tool might be applied to the study of clinical progress and outcome by therapists during CAVES and related CAVEAT treatment, and (2) how more body-focused therapeutic techniques might further enhance the CAVES/CAVEAT model in future clinical applications and research.